Seymour and Henry - Lewis, Kim, 1951- (Somerville, Mass. : Candlewick Press, 2009)
Ducklings Seymour and Henry hide from their mother when she tells them it is time to go home, but when it starts to rain their game does not seem like much fun anymore.
1.4
K-3
Keywords: Ducks -- Juvenile fiction; Mother and child -- Juvenile fiction; Rain and rainfall -- Juvenile fiction; Ducks -- Fiction; Mother and child -- Fiction; Rain and rainfall -- Fiction; Ducks -- Fiction; Mother-child relationship -- Fiction; Rain -- Fiction